2018
DOI: 10.1007/978-3-030-01267-0_20
|View full text |Cite
|
Sign up to set email alerts
|

Variational Wasserstein Clustering

Abstract: We propose a new clustering method based on optimal transportation. We discuss the connection between optimal transportation and k-means clustering, solve optimal transportation with the variational principle, and investigate the use of power diagrams as transportation plans for aggregating arbitrary domains into a fixed number of clusters. We drive cluster centroids through the target domain while maintaining the minimum clustering energy by adjusting the power diagram. Thus, we simultaneously pursue clusteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Effective use of such topological descriptors requires a notion of proximity that quantifies the similarity between persistence barcodes, a convenient representation for connected components and cycles [Ghrist, 2008]. Wasserstein distance, which measures the minimal effort to modify one persistence barcode to another [Rabin et al, 2011], is an excellent choice due to its appealing geometric properties [Staerman et al, 2021] and its effectiveness shown in many machine learning applications [Kolouri et al, 2017, Mi et al, 2018, Solomon et al, 2015. Importantly, Wasserstein distance can be used to interpolate networks while preserving topological structure [Songdechakraiwut et al, 2021], and the mean under the Wasserstein distance, known as Wasserstein barycenter [Agueh and Carlier, 2011], can be viewed as the topological centroid of a set of networks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective use of such topological descriptors requires a notion of proximity that quantifies the similarity between persistence barcodes, a convenient representation for connected components and cycles [Ghrist, 2008]. Wasserstein distance, which measures the minimal effort to modify one persistence barcode to another [Rabin et al, 2011], is an excellent choice due to its appealing geometric properties [Staerman et al, 2021] and its effectiveness shown in many machine learning applications [Kolouri et al, 2017, Mi et al, 2018, Solomon et al, 2015. Importantly, Wasserstein distance can be used to interpolate networks while preserving topological structure [Songdechakraiwut et al, 2021], and the mean under the Wasserstein distance, known as Wasserstein barycenter [Agueh and Carlier, 2011], can be viewed as the topological centroid of a set of networks.…”
Section: Introductionmentioning
confidence: 99%
“…The high cost of computing persistence barcodes, Wasserstein distance and the Wasserstein barycenter limit their applications to small scale problems, see, e.g., [Clough et al, 2020, Hu et al, 2019, Kolouri et al, 2017, Mi et al, 2018. Although approximation algorithms have been developed [Cuturi, 2013, Cuturi and Doucet, 2014, Lacombe et al, 2018, Li et al, 2020, Solomon et al, 2015, Vidal et al, 2019, Xie et al, 2020, Ye et al, 2017, it is unclear whether these approximations are effective for clustering complex networks as they inevitably limit sensitivity to subtle topological features.…”
Section: Introductionmentioning
confidence: 99%
“…An approach to empirical distribution clustering via k-means is also given in Henderson, Gallagher and Eliassi-Rad [HGER15] in a non-financial context. Other works have utilised the Wasserstein distance for clustering problems, see for instance [LW08,YWWL17], where in the latter distributions are represented as weight-mass pairs, and clustering is considered in the context of images and documents, or [MZGW18] for an approach using variational optimal transport. Such approaches are similar to the work in this paper as they often employ classic unsupervised learning algorithms with some modification that allows them to handle distributional datum.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, by generalizing our prior work on volumetric Wasserstein distance computation (Mi et al 2017(Mi et al , 2018, we propose a framework to compute the volumetric Wasserstein distance of structural MR images and explore its application as a potential univariate neurodegenerative biomarker. With the proposed framework, a volumetric Wasserstein distance will be computed for each MR image from its optimal transportation (OT) map to the template image.…”
Section: Introductionmentioning
confidence: 99%